Implication of incomplete contract (IC) Malaysian private finance initiative (PFI) - Mansor, Nur Syaimasyaza; Abdul Rashid, Khairuddin; Ayob, Mohd Fairullazi; Hasan, Sharina Farihah (Construction Research Institute of Malaysia (CREAM), 2019)
Theoretically, contracts are inevitably incomplete. Incomplete contract (IC) is characterized by the absence of clearly defined, in its entirety, ex-ante the parties’ requirements, rights and obligations and there are gaps, missing provisions, and ambiguities in its terms. On the one hand, IC exposes the contracting parties to the risk of opportunistic behavior, haggling, and disputes, but on the other hand, it allows flexibility to deal with uncertainty and change. Private Finance Initiative (PFI) contracts in Malaysia also cannot avoid being incomplete and there are twelve (12) clauses that contribute to the incompleteness. Literature review and two-round modified Delphi method were carried out to assess IC’s implication in Malaysian PFI concession contracts. This paper aims to report on the said assessment. The findings showed that the presence of IC in PFI projects in Malaysia causes positive and/or negative implications. Most of the positive implications mentioned on the flexibility of the incomplete clause to deal with future changes and provide the parties opportunity to renegotiate. Meanwhile, many negative implications refer to delay, disputes, and the risk of opportunistic behavior. Input from this paper will facilitate contract designers, and those involved in PFI projects in emphasizing or giving attention to the aspect that contributes to contracting incompleteness and its implications and consequently improves the provisions when drafting new contracts.